Highway investment in developing countries proceedings of the conference 'Criteria for planning highway investment in developing countries', sponsored by the Commission of the European Communities and the Institution of Civil Engineers ; organised by the Institution of Civil Engineers and held at the Cafe Royal Conference Centre, London, on 17-18 May 1982. (Thomas Telford, 1983)
An examination of criteria for planning highway investment in developing countries.